The effect of a combined intervention of Qur’an recitation, effleurage massage, and autogenic relaxation on pain reduction in patients with gastritis - Anggraini, Choriah Geby; Dirdjo, Maridi Marsan; Nurjannah, Misbah; Satria, Andri Praja (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Gastritis is an inflammation of the gastric mucosa that is generally caused by irregular eating patterns, which can trigger increased gastric acid production. Gastritis remains a global health problem due to the high number of cases, including in Kutai Kartanegara, Indonesia. One of the nursing efforts to help reduce patient complaints is the application of complementary therapy to decrease the degree of pain in patients with gastritis. Purpose: To analyze the intervention of Qur’an recitation therapy combined with effleurage massage and autogenic relaxation in reducing epigastric pain in patients with gastritis. Method: A quasi-experimental study. The data used were primary data obtained through observation and intervention using nursing care instruments for patients with gastritis. The study was conducted in December 2025 at Aji Muhammad Parikesit Tenggarong Regional General Hospital. The sample consisted of one intervention patient and two control patients. Data were collected through observation, interviews, and case documentation. The results were presented descriptively by comparing the degree of pain reduction between the intervention patient and the control patients. Results: The patient with gastritis who received the combination of Qur’an recitation therapy, effleurage massage, and autogenic relaxation appeared to experience a more marked reduction in epigastric pain than the control patients. The intervention patient showed a decrease in pain scale from moderate to mild, accompanied by improved comfort and relaxation, whereas the control patients showed smaller reductions in pain intensity. Conclusion: The nursing innovation intervention showed potential to support faster and more optimal pain reduction in patients with gastritis.